A framework for reaching common understanding during sketching in design teams - N. S. Nik Ahmad Ariff; P. Badke-Schaub,; O. Eris; S. S. S. Suib (2012)
Theoretical and empirical levels, and propose two frameworks. The first one, the design communication block framework, categorizes the types of activities that take place during sketching, and constitutes the analysis scheme for the empirical dimension of the work. The second framework, a framework for reaching common understanding during sketching in design teams, embodies the outcomes of our analysis. Our main finding is that although drawing activity itself forms the basis of team discourse during sketching, explaining, detailing and transfer activities make ideas more concrete, understandable and transferrable within the team. Our findings also show that when verbal communication is blocked, the distinction between drawing activity, and explaining, detailing and transfer activities become even clearer.